Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.1 - Simplifying Rational Expressions - Exercise Set: 68


Answer is correct. $\frac{x+2}{-8x-1}$

Work Step by Step

Answer is correct. $\frac{2-15x-8x^{2}}{64x^{2}-1}$= $\frac{2+x-16x-8x^{2}}{64x^{2}-1}$= $\frac{1(2+x)-8x(2+x)}{(8x)^{2}-1^{2}}$= $\frac{(1-8x)(2+x)}{(8x)^{2}-1^{2}}$= $\frac{(1-8x)(2+x)}{(8x+1)(8x-1)}$= $\frac{(1-8x)(2+x)}{(8x+1)(-1)(1-8x)}$= $\frac{(2+x)}{(8x+1)(-1)}$= $\frac{x+2}{-8x-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.